Handbook of switchgears (McGraw-Hill handbooks, 2007)
Offers electrical power engineers and technicians a guide to the basic design, operation, and protection of switchgears, including circuit breakers, transformers, and fuses. Containing contributions by experts from Bharat Heavy Electricals Limited, this book guides readers through switchgears for electrical power grids and industrial facilities.